Specifics of Determining the Market Assessment Rights Requirement for Obligations Arising from the Implementation of the Bank Credit Operations of Different Quality that are Secured and Unsecured Collaterally - Stolyarov, V.F.; Artemenko, D.M. (Економічний вісник Донбасу, 2015)
This article offers the standardized mechanisms of the market assessment rights requirement for obligations of different quality categories arising as a result of the bank credit operations implementation. Specific approaches and assessment methods are relevant both to the existing legislation of the professional appraisal activity implementation in Ukraine and to national and international assessment standards, and meet the criteria of the National Bank of Ukraine on the calculation of credit risk. The proposed assessment model allows to determine the assessment rights requirement for obligations by the formed credit portfolio of the bank at minimum cost and the lack of sufficient information concerning the object assessment. У статті запропоновані уніфіковані механізми оцінки прав вимоги за зобов'язаннями різних категорій якості, що виникають внаслідок здійснення банком кредитних операцій. Конкретні підходи та методи оцінки, відповідають чинному законодавству щодо здійснення професійної оціночної діяльності в Україні, а також національним і міжнародним стандартам оцінки та задовольняють вимогам положень Національного банку України про порядок розрахунку ризику кредиту. Запропонована модель оцінки дозволяє визначити вартість прав вимоги зобов'язань за сформованим кредитним портфелем банку, за мінімальних витрат та браком достатньої інформації відносно об'єкту оцінки. В статье предложены унифицированные механизмы оценки прав требования по обязательствам различных категорий качества, возникающих в результате осуществления банком кредитных операций. Конкретные подходы и методы оценки, соответствуют действующему законодательству по осуществлению профессиональной оценочной деятельности в Украине, а также национальным и международным стандартам оценки и удовлетворяют требованиям положений Национального банка Украины о порядке расчета риска кредита. Предложенная модель оценки позволяет определить стоимость прав требования обязательств по сложившемуся кредитному портфелю банка, при минимальных затратах и нехватке достаточной информации относительно объекта оценки.